Exact closed-form solution to jet flow of a polymer arising in the electrospun nanofiber elaboration process - Van Gorder, R (Elsevier, 2015)

(untitled)
In the present paper, we obtain the exact solution to the jet flow of a polymer arising in the electrospun nanofiber elaboration process. This allows us to improve on the approximate solutions of Colantoni and Boubaker (2014) and He, Kong, Chen, Hu, and Chen (2014). Our corrected and far simpler solution is more useful for extracting the salient physics inherent in the electrospun nanofiber elaboration process. We then consider the more robust formulation of the problem, in which the velocity of the jet and the radius of the jet depend strongly on one another, obtaining the solution in this case as well. All of the results obtained are rather simple, and give us closed-form exact solutions (rather than complicated approximations), and hence these results both maintain accuracy and have the possibility of being useful for future studies into the physics of such mechanical processes. The results also agree nicely with experimental and numerical results present in the literature.